PENGARUH SISTEM PENGENDALIAN INTERNAL, FUNGSI AUDIT INTERNAL DAN SISTEM INFORMASI AKUNTANSI TERHADAP KREDIT BERMASALAH PADA PT. BANK SULUT GO - Sepang, Juvenalis Paulus; Ilat, Ventje; Morasa, Jenny (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2021)
Every form of credit disbursement carries the risk of non-performing loans. Non-performing loans are a condition where the customer is unable to pay part or all of his obligations to the bank as agreed. This study aims to analyze and empirically prove the effect of the implementation of the internal control system, internal audit function, and accounting information system on non-performing loans at PT. North Sulawesi Bank. This type of research is quantitative research, using primary data through questionnaires. Respondents in this study were employees at PT. North Sulawesi Bank. The population used is all employees in 26 Branch Offices and 6 Sub-Branches of PT. Bank SulutGo, totaling 213 employees. while the sample used is as many as 120 respondents. The data were analyzed using multiple linear regression analysis and data testing was carried out with the help of the SPSS version 22 program. The results showed that: 1). The application of the internal control system has a negative and significant effect on non-performing loans at PT. North Sulawesi Bank. 2). The internal audit function has a negative and significant effect on non-performing loans at PT. North Sulawesi Bank. 3). The accounting information system has a negative and significant effect on non-performing loans at PT. North Sulawesi Bank. The value of the determinant coefficient is 0.680. This shows that the magnitude of the influence of the independent variables, namely the implementation of the internal control system, internal audit function, and accounting information system on the dependent variable, namely non-performing loans explained by the equation model in this study, is 68.00%. While the remaining 32.00%.